Circadian blood pressure profile and cardiovascular risk factors in young people - M. E. Evsevyeva; O. V. Sergeeva; G. P. Nikulina; M. V. Rostovtseva; N. V. Orekhova (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To study the associations between 24-hour blood pressure monitoring (BPM) results and selected cardiovascular risk factors in young people.Material and methods. In total, 204 students of Stavropol State Medical Academy were examined - 80 men and 124 women (mean age 20,3+0,32 years). Questionnaire survey focused on family history, health behaviours, psychological problems, and self-evaluated health. Anthropometry parameters, blood pressure, BP levels (measured by office and 24-hour BPM methods), and lipid profile were also assessed. According to the number of cardiovascular risk factors (CVD RF) diagnosed, all participants were divided into three groups: Group I - no CVD RF; Group II - one CVD RF; Group III - 2 or more VD RF.Results. No CVD RF were observed in 25% of the participants. Most subjects had one CVD RF (34% males, 59,7% females), two CVD RF (32% and 11,7%), or three and more CVD RF (5,2% and 1,3%, respectively). Increase in CVD RF number was associated with elevated mean circadian levels of systolic (SBP), diastolic (DBP), mean (mBP) and pulse BP (PBP).Conclusion. In young men and women, an association between CVD RF number and circadian BP levels was observed. Specifically, increased CVD RF number was linked to elevated mean circadian, mean daytime and mean nighttime SBP, DBP, mBP, and PBP.